Are There Protective Genes for Disc Degeneration?. (May 2014) - Zhang, Joyce; Xiong, Serena; Chan, Wilson; Tam, Vivian; Sakai, Daisuke; Chan, Danny
Intervertebral disc degeneration is a major cause of back pain with a huge impact to the quality of life as we age. It is clear from studies that there is a significant genetic contribution to the susceptibility of an individual to disc degeneration. Indeed, several genetic risk factors have been identified that included extracellular matrix proteins and enzymes that modify these proteins. These genetic risk factors interact with the environment that impact on the onset, severity, and symptomatic outcomes. In a population study in Hong Kong, whereas over 90% of most people will succumb to some form of disc degeneration by the age of 50 years, there are individuals who showed no indication of disc degeneration by MRI suggesting the possibility of "protective factors, " either genetic and/or environmental. 1 It is likely that genetics would play a role in protective mechanisms. It is possible to study potential protective genes in human using case-control association studies, but it would require the collection of a very large cohort of "protected" individuals. Another approach is to study in animal models and mapped the identified loci to the human genome. In mice, there are "super healer" strains with superior healing potentials of damaged tissues including elastic cartilage of the ear and hyaline cartilage of synovial joints. 2 Whether these healing potentials translate to protective mechanisms of the intervertebral disc is not clear and has not been studied. Our initial analysis comparing good healer (Lg/J and MRL) with poor healer (Sm/J and C57B) strains of mice suggests that there should be protective genes influencing the homeostasis of the nucleus pulposus and the annulus fibrosus. A gene discovery study has been performed for knee joint cartilage repair in these mice and potential genetic loci for improved cartilage repair identified. 3, 4 Thus, with the establishment of appropriate phenotypic traits for the intervertebral disc, it is possible to search for protective/repair genes for the disc. There should be "protective genes"; what is important is finding the appropriate animal models and human cohorts for genetic studies and validation. Focusing on protective genes and understanding the molecular and cellular controls involved in delaying the onset and progression of intervertebral disc degeneration may serve to be a better approach in developing therapeutic treatments and preventative strategies. Disclosure of Interest None declared References Jim JJ, Noponen-Hietala N, Cheung KM, et al. The TRP2 allele of COL9A2 is an age-dependent risk factor for the development and severity of intervertebral disc degeneration. Spine 2005;30(24):2735–2742 Fitzgerald J, Rich C, Burkhardt D, Allen J, Herzka AS, Little CB. Evidence for articular cartilage regeneration in MRL/MpJ mice. Osteoarthritis Cartilage 2008;16(11):1319–1326 Rai MF, Hashimoto S, Johnson EE, et al. Heritability of articular cartilage regeneration and its association with ear wound healing in mice. Arthritis Rheum 2012;64(7):2300–2310 Rai MF, Schmidt EJ, McAlinden A, Cheverud JM, Sandell LJ. Molecular insight into the association between cartilage regeneration and ear wound healing in genetic mouse models: targeting new genes in regeneration. G3 (Bethesda) 2013;3(11):1881–1891